Nourishing intervention impact with Medicago sativa L (alfalfa) protein extract in chronically undernourished preschool children - Soberón, María (2009)
Introduction: Studies made at preclinical level have demonstrated the Medicago sativa L, alfalfa (CPA)’s concentrated protein biological value; as such this product could be an alternative to reduce undernourishment. Objective: To determine CPA consuming effects in kindergarten children with chronic undernourishment by biochemical and hematologic indicators. Design: Intervention analytical, longitudinal and prospective study. Setting: Biochemistry and Nutrition Research Center, Faculty of Medicine, Universidad Nacional Mayor de San Marcos. Participants: Pampas, Huancavelica, Peru, preschool children with chronic undernourishment. Interventions: Previous parents informed consent we determined the nourishment-nutritional, biochemical and hematologic status of 23 less than six year-old children in order to establish undernourishment. Then a CPA nutritional nourishment intervention in the chronically undernourished children was developed for 25 days and finally the initial evaluation was repeated. Biochemical -hemoglobin, total proteins, albumin and globulin, creatinine, transaminases- and hematologic -hematocrit, reticulocytes count- determinations were done before and after providing the CPA nutritional complement. Excel program and t-student were used in order to obtain results inference. Results: By stature/age indicator 84,5% of the children suffered chronic undernourishment. With respect to calorie and nutrients consumed by the children, energy values were between 563 kcal and 2 597 kcal, protein 9,7 g to 78 g, lipids 5,1 g to 53,8 g, carbohydrates from 79,8 g to 495,1 g, calcium between 180,9 mg and 986 mg, and iron from 1,9 mg to 21,5 mg. Hemoglobin, total proteins, globulins, creatinine, transaminases and hematocrit before and after CPA ingestion did not display variations (p>0,05) but albumin and reticulocytes count increased significantly following ingestion (p<0,05). Conclusions: CPA daily consumption for 25 days CPA by children with chronic undernourishment significantly increased reticulocytes count and albumin levels.